2017
DOI: 10.1088/1361-6595/aa9b3b
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the helium plasma jet delivery of reactive species into a 3D cancer tumour

Abstract: Cold atmospheric plasmas have attracted significant worldwide attention for their potential beneficial effects in cancer therapy. In order to further improve the effectiveness of plasma in cancer therapy, it is important to understand the generation and transport of plasma reactive species into tissue fluids, tissues and cells, and moreover the rates and depths of delivery, particularly across physical barriers such as skin. In this study, helium (He) plasma jet treatment of a 3D cancer tumour, grown on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 132 publications
1
56
1
Order By: Relevance
“…It is seen that the T v and T r values are similar for the positive and negative pulsed plasma jets and did not significantly vary with pulse width, with values of approximately 0.3 eV and 0.03 eV, respectively. The T v and T r values are higher than we recently measured for similar plasma jet configurations operated with a high-voltage bipolar square wave pulse in two separate studies [34,39]; this is despite a lower applied voltage used in this present study compared to the previous two studies. The reason for the higher T v and T r values in this study is because of an increase in the population of higher energetic electrons with a rapid change in the voltage amplitude.…”
Section: Plasma Parameters and Phcontrasting
confidence: 77%
“…It is seen that the T v and T r values are similar for the positive and negative pulsed plasma jets and did not significantly vary with pulse width, with values of approximately 0.3 eV and 0.03 eV, respectively. The T v and T r values are higher than we recently measured for similar plasma jet configurations operated with a high-voltage bipolar square wave pulse in two separate studies [34,39]; this is despite a lower applied voltage used in this present study compared to the previous two studies. The reason for the higher T v and T r values in this study is because of an increase in the population of higher energetic electrons with a rapid change in the voltage amplitude.…”
Section: Plasma Parameters and Phcontrasting
confidence: 77%
“…On the basis of the comparison between the plasma treatment and H 2 O 2 , NO 2 − , and NO 3 − treatment, the possible anticancer mechanism can be postulated. As shown in Figure e, owing to the protection by the 3D‐organized extracellular matrix and neighboring cells, only long‐lived RONS such as H 2 O 2 , NO 3 − , and NO 2 − may play a key role in plasma‐induced anticancer effects . These long‐lived RONS cross cell membranes by diffusion or through aquaporins and affect A549 cells .…”
Section: Resultsmentioning
confidence: 99%
“…[ 66 ] It was recently proposed that CAP can induce apoptosis inside a tumor by the delivery of peroxides and nitrites coupled with aqueous oxygen, which is also responsible for the increase of oxygen tension in the hypoxic tissue. [ 67,68 ] Accordingly, in vivo data showed that a plasma jet source increased both blood flow and tissue oxygen partial pressure. [ 69 ]…”
Section: Discussionmentioning
confidence: 99%